Research on the protection and restoration technology of glazed components in ancient architecture - Yao Chen; Liwen Yu; Liping Chen; Linzi Ouyang; Ning Wang (PLoS ONE, 2026)
In traditional Chinese architecture, glazed tile components are a significant decorative element that are frequently utilized on walls and roofs. However, glazed tile components typically show variable degrees of deterioration and damage owing to long-term exposure to the natural environment. This study examines and evaluates the preservation quality and primary forms of deterioration of historic architectural glazed tile components. The damage development process of glazed tile components under the combined influences of temperature, humidity fluctuations, and acidic environments was discovered through characterization of material morphological changes and corrosion products. Tetraethyl orthosilicate (TEOS) and hydroxyl-terminated polydimethylsiloxane (PDMS−OH) were chosen as reinforcement materials for common problems including pulverization of the glazed tile body. The glazed tile body was reinforced using ethanol as a solvent. The best material formulation for glazed tile body reinforcement was chosen by evaluating the performance of reinforcement systems with various ratios using a thorough index analysis. Concurrently, scanning electron microscopy (SEM) and X-ray photoelectron spectroscopy (XPS) were used to examine the reinforcing process. This work suggests modifying the matrix material’s particle size to improve mechanical characteristics and structural stability for glazed tile components that are extensively damaged and challenging to repair with reinforcement. The study’s findings can serve as a theoretical foundation and technical guide for the scientific preservation and repair of glazed tile elements found in historic buildings.